Influência da composição química do substrato no cultivo de Pleurotus florida - Figueiró, Gláucia Garcia; Graciolli, Luiz Antônio [UNESP] (Editora da Universidade Federal de Lavras (UFLA), 2011)
Com o objetivo de avaliar a influência da composição química do substrato no cultivo do cogumelo comestível Pleurotus florida, seis resíduos agrícolas foram testados: palha de arroz, palha de feijão, palha de trigo, folha de bananeira, palha de sorgo e sabugo de milho. O substrato palha de feijão apresentou resultados semelhantes para a produção (189,8 g kg-1), eficiência biológica (89,2%) e número de cogumelos (12) à palha de arroz, substrato utilizado tradicionalmente no cultivo de Pleurotus em escala comercial. Não foi possível atribuir apenas a um fator químico as altas produções e eficiências biológicas observadas em palha de arroz e palha de feijão e muito menos para a baixa produção em palha de sorgo (77,8 g kg-1) e sabugo de milho (53,2 g g-1). No geral, substratos com relação C/N em torno de 45 (N = 1,0%), maior conteúdo de cinzas, acrescido de altos teores de P, K, Ca, Mg and Mn foram os melhores para o cultivo de P. florida.

The purpose of this work was to evaluate the influence of the chemical composition of the substrate in the cultivation of the edible mushroom Pleurotus florida. Six agricultural by-products were tested: rice straw, bean straw, wheat straw, banana leaf, sorghum straw and maize cobs. Using bean straw as the substrate showed similar results for yield (189.8 g kg-1), biological efficiency (89.2%) and number of mushrooms (12) as rice straw substrates traditionally used for the cultivation of Pleurotus on a commercial scale. It was not possible to attribute the high yields and biological efficiency observed in rice and bean straw solely to chemical factors and, even less so for the low yields presented by sorghum straw (77.8 g kg-1) and maize cobs (53.2 g kg-1). In general, substrates with C/N ratio around 45 (N = 1.0%), high ash content and high levels of P, K, Ca, Mg and Mn were the best for the cultivation of P. florida.
Influence of the chemical composition of the substrate in the cultivation of Pleurotus florida
Keywords: Cogumelo ostra; resíduos agrícolas; eficiência biológica; produção; Oyster mushroom; agricultural waste; biological efficiency; production